Platelet-to-lymphocyte and neutrophil-to-lymphocyte ratios as noninvasive predictors for renal involvement in systemic lupus erythematosus in health clinics - Mona M Soliman; Yasmine S Makarem; Ahmed A El Wafaa; Marwa K.A Khairallah (SpringerOpen, 2019)
Objective Renal injury is a prevalent complication related to lupus erythematosus and its occurrence is linked with bad alarms. Yet, a noninvasive procedure to predict renal impairment in health clinics has not been settled. Consequently, the authors postulated that platelet-to-lymphocyte (PLR) ratio and neutrophil-to-lymphocyte ratio (NLR) might be used as valid noninvasive indicators for kidney impairment. Participants and methods In this cross-sectional research, 270 participants were enrolled into the research after exclusion of 70 patients; the included patients were classified into four groups: 80 patients with lupus nephritis (LN) diagnosed by renal biopsy, 12 active lupus patients without renal involvement, 28 lupus patients on remission, and 80 healthy participants as controls. The authors evaluated levels of PLR and NLR in addition to other renal and lupus markers. Results The results have shown that PLR and NLR had significantly higher levels in active lupus patients as in biopsy-proven LN in comparison to inactive systemic lupus erythematosus and control groups. NLR was positively correlated with serum creatinine in patients with LN; however, they did not show significant association with other predictors of renal diseases. The study demonstrated that PLR and NLR had significant association to advanced classes of LN. Furthermore, the receiver-operating characteristic curve showed a higher sensitivity of PLR in early detection of kidney function impairment in LN patients (88.9%) while NLR showed more specificity (87.5%). Conclusion PLR and NLR could act as noninvasive markers for detection of renal involvement in lupus patients in health clinics as for the prediction of renal pathological class.